Bridging the Gap: University Support and the Role of Industrial Apprentice Culture for Student Employability - Marpaung, Alexander Batara; Purba, John Tampil; Tukiran, Martinus (Journal of Cultural Analysis and Social Change, 2025)
Universities today face increasing pressure to prepare graduates who are immediately capable of contributing in a fast-shifting labour market. This research explores how leadership, curriculum relevance, lecturer expertise, and campus infrastructure collectively shape graduate employability. It also evaluates how quality management systems (QMS) and a campus culture that supports apprenticeship experiences serve as mediators in this process. A quantitative approach using PLS-SEM was applied to survey data from 335 students enrolled at leading private universities in Indonesia. Findings highlight that strong academic leadership and competent lecturers play central roles in improving institutional quality and building a campus environment that values experiential learning. Both QMS and apprenticeship-supportive culture significantly contribute to employability outcomes, with cultural factors showing stronger influence. The findings highlight that employability is not an automatic outcome of education but a strategically structured process supported by institutional leadership, curriculum innovation, and a deeply embedded organisational culture that values experiential learning. The paper offers practical recommendations for university leaders and policymakers to strengthen institutional systems and learning culture in support of graduate readiness.